Aggressive network self-defense - Wyler, Neil R. (Rockland, MA : Syngress Pub., 2005)
Are you tired of feeling vulnerable to the latest security vulnerabilities? Are you fed up with vendors who take too long to release security patches, while criminals waste no time in exploiting those very same holes? Do you want to know who, exactly, is really trying to hack your network? Do you think EVERYONE should be responsible for securing their owns systems so they can't be used to attack yours? Do you think you have the right to defend yourself, your network, and ultimately your business against aggressors and adversaries? If so, Aggressive Network Self-Defense is the book for you. Le.
Introduction: -- What's in a hat? -- Chapter 1: Is it Legal to Strike Back? -- Chapter 2: Automated Strike Back Worms -- Chapter 3: Targeting an Attacking Host -- Chapter 4: Aggressive Intrusion Prevention Systems Chapter 5: Honey Pots and Honey Nets -- Chapter 6: Windows Insecurity: Shattering the Glass. Chapter 7: Disinformation Campaigns -- Chapter 8: Cyber Terrorism and Counter Intelligence Chapter 9: Know Your Enemy: Social Engineering Chapter 10: Google This! -- Chapter 11: When Enough is Enough.
Includes bibliographical references and index.
Keywords: Internet -- Security measures; Computer security; Electronic books